Global solar radiation and energy yield estimation from photovoltaic power plants for small loads. Issue 5 (9th April 2017) - Sahin, Ahmet Z.; Rehman, Shafiqur; Al-Sulaiman, Fahad
ABSTRACT: Daily global solar radiation on a horizontal surface and duration of sunshine hours have been determined experimentally for five meteorological stations in Saudi Arabia, namely, Abha, Al-Ahsa, Al-Jouf, Al-Qaisumah, and Wadi Al-Dawaser sites. Five-years of data covering 1998–2002 period have been used. Suitable Angstrom models have been developed for the global solar radiation estimation as a function of the sunshine duration for each respective sites. Daily averages of monthly solar PV power outputs have been determined using the Angstrom models developed. The effect of the PV cell temperature on the PV efficiency has been considered in calculating the PV power output. The annual average PV output energy has been discussed in all five sites for small loads. The minimum and maximum monthly average values of the daily global solar radiation are found to be 12.09 MJ/m 2 /d and 30.42 MJ/m 2 /d for Al-Qaisumah and Al-Jouf in the months of December June, respectively. Minimum monthly average sunshine hours of 5.89 hr were observed in Al-Qaisumah in December while a maximum of 12.92 hr in Al-Jouf in the month of June. Shortest range of sunshine hours of 7.33–10.12 hr was recorded at Abha station. Minimum monthly average Solar PV power of 1.59 MJ/m 2 /day was obtained at Al-Qaisumah in the month of December and a maximum of 3.39 MJ/m 2 /day at Al-Jouf in June. The annual PV energy output was found to be 276.04 kWh/m 2, 257.36 kWh/m 2, 256.75 kWh/m 2, 245.44 kWh/m 2, and 270.95 kWh/m 2 at Abha, Al-Ahsa, Al-Jouf, Al-Qaisumah, and Wadi Al-Dawaser stations, respectively. It is found that the Abha site yields the highest solar PV energy among the five sites considered.